2022
DOI: 10.7759/cureus.30806
|View full text |Cite
|
Sign up to set email alerts
|

Hook Plate Versus Distal Locking Plate for the Fixation of Unstable Distal Clavicle Injuries, Outcomes and Complications: A Meta-Analysis

Abstract: Numerous interventions are advised for the surgical management of distal clavicle fractures. Hook plate (HP) and distal locking plate (DLP) are among the commonly used techniques; nonetheless, no single procedure is deemed to be the benchmark treatment. Thus, the aim of the study is to conduct a comparative analysis, hopefully, to recommend the superior method between the two operations.PubMed, Embase via Ovid and Web of science were electronically searched between January 2000 and to date for studies directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…Malik et al [16] reported that the shoulder function scores after arthroscopically assisted CC ligament reconstruction ranged from 81.8 to 96.2, as assessed by the Constant-Murley score (CMS). For other fixation methods, the mean CMS was 85.3 to 88 in the TBW group [23,24], 79.9 to 93.3 in the hook plate group, and 82.8 to 98.1 in the locking plate group [25,26]. The present method accomplished relatively better ROM recovery and better clinical outcomes compared with similar methods and other fixation methods, suggesting that arthroscopically assisted CC ligament reconstruction can be an optimal treatment for lateral clavicle fractures accompanied by ligament injury.…”
Section: Discussionmentioning
confidence: 96%
“…Malik et al [16] reported that the shoulder function scores after arthroscopically assisted CC ligament reconstruction ranged from 81.8 to 96.2, as assessed by the Constant-Murley score (CMS). For other fixation methods, the mean CMS was 85.3 to 88 in the TBW group [23,24], 79.9 to 93.3 in the hook plate group, and 82.8 to 98.1 in the locking plate group [25,26]. The present method accomplished relatively better ROM recovery and better clinical outcomes compared with similar methods and other fixation methods, suggesting that arthroscopically assisted CC ligament reconstruction can be an optimal treatment for lateral clavicle fractures accompanied by ligament injury.…”
Section: Discussionmentioning
confidence: 96%
“…Malik et al [ 23 ] reported that shoulder function scores after arthroscopically assisted CC ligament reconstruction ranged from 81.8 to 96.2, as assessed through the Constant–Murley score. For other fixation methods, the mean Constant–Murley score ranged from 85.3 to 88 in the TBW group [ 35 , 36 ], from 79.9 to 93.3 in the hook plate fixation group, and from 82.8 to 98.1 in the locking plate fixation group [ 25 , 37 ]. On the basis of these scores, arthroscopically assisted CC ligament reconstruction may be superior to other surgical procedures.…”
Section: Discussionmentioning
confidence: 99%